Guidelines for instructional design of courses for the development of self-regulated learning for teachers - Ortega-Ruipérez, Beatriz; Castellanos-Sánchez, Almudena (South African Journal of Education, 2024)
Self-regulated learning strategies are essential for learning, and to teach learners to use them, teachers must master them. The objective of this study was to identify training priorities for including these strategies in online courses for teachers, and to determine whether opinion influences the use of strategies. The design was non-experimental and cross-sectional, and involved administering the revised Cuestionario de Evaluación de las Estrategias de Aprendizaje de los Estudiantes Universitarios (CEVEAPEU questionnaire) to 285 teachers. The results allow us to differentiate between priority weaknesses, lower-priority weaknesses, and strengths in relation to metacognitive strategies (planning, objectives, self-evaluation, self-regulation, and context). To determine this, a frequency analysis was used, followed by a Mann-Whitney U (for 2-group variables) and Kruskal-Wallis (for 3 groups) test to determine whether opinion influences the use of strategies. Priority weaknesses were identified in the knowledge of objectives and evaluation criteria (planification); the ability to recognise when an exam has been passed (self-evaluation); modifying initial plans, dedicating more effort to difficult subjects, and learning new study techniques (self-regulation); and taking advantage of study time (context control). We concluded that opinions on self-regulated learning influence the use of strategies. Finally, work should be done on the recognition of the importance of self-regulated learning, time management strategies, self-evaluation techniques, flexibility, and self-control.
Keywords: distance education; learning to learn; metacognition; self-regulated learning; teacher education; Scopus; WOS